Bacterial Diversity and Biogeochemistry of Two Marine Shallow-Water Hydrothermal Systems off Dominica (Lesser Antilles) - Pop Ristova, Petra; Pichler, Thomas; Friedrich, Michael W.; Bühring, Solveig I. (Frontiers in Microbiology, 2017)
Shallow-water hydrothermal systems represent extreme environments with unique biogeochemistry and high biological productivity, at which autotrophic microorganisms use both light and chemical energy for the production of biomass. Microbial communities of these ecosystems are metabolically diverse and possess the capacity to transform a large range of chemical compounds. Yet, little is known about their diversity or factors shaping their structure or how they compare to coastal sediments not impacted by hydrothermalism. To this end, we have used automated ribosomal intergenic spacer analysis (ARISA) and high-throughput Illumina sequencing combined with porewater geochemical analysis to investigate microbial communities along geochemical gradients in two shallow-water hydrothermal systems off the island of Dominica (Lesser Antilles). At both sites, venting of hydrothermal fluids substantially altered the porewater geochemistry by enriching it with silica, iron and dissolved inorganic carbon, resulting in island-like habitats with distinct biogeochemistry. The magnitude of fluid flow and difference in sediment grain size, which impedes mixing of the fluids with seawater, were correlated with the observed differences in the porewater geochemistry between the two sites. Concomitantly, individual sites harbored microbial communities with a significantly different community structure. These differences could be statistically linked to variations in the porewater geochemistry and the hydrothermal fluids. The two shallow-water hydrothermal systems of Dominica harbored bacterial communities with high taxonomical and metabolic diversity, predominated by heterotrophic microorganisms associated with the Gammaproteobacterial genera Pseudomonas and Pseudoalteromonas, indicating the importance of heterotrophic processes. Overall, this study shows that shallow-water hydrothermal systems contribute substantially to the biogeochemical heterogeneity and bacterial diversity of coastal sediments.